NIR‐II Ratiometric Chemiluminescent/Fluorescent Reporters for Real‐Time Monitoring and Evaluating Cancer Photodynamic Therapy Efficacy - Su, Lichao; Chen, Yiming; Huo, Hongqi; Liao, Naishun; Wu, Ying; Ge, Xiaoguang; Guo, Zhiyong; Chen, Zhongxiang; Zhang, Xuan; Song, Jibin (Small (Weinheim an der Bergstrasse, Germany), 2022)
The development of probes for early monitoring tumor therapy response may greatly benefit the promotion of photodynamic therapy (PDT) efficacy. Singlet oxygen (1O2) generation is a typical indicator for evaluating PDT efficacy in cancer. However, most existing probes cannot quantitatively detect 1O2 in vivo due to the high reactivity and transient state, and thus have a poor correlation with PDT response. Herein, a 1O2‐responsive theranostic platform comprising thiophene‐based small molecule (2SeFT‐PEG) and photosensitizer Chlorin e6 (Ce6) micelles for real‐time monitoring PDT efficacy is developed. After laser irradiation, the Ce6‐produced 1O2 could simultaneously kill cancer and trigger 2SeFT‐PEG to produce increased chemiluminescence (CL) and decreased fluorescence (FL) signals variation at 1050 nm in the second near‐infrared (NIR‐II, 950–1700 nm) window. Significantly, the ratiometric NIR‐II CL/FL imaging at 1050 nm could effectively quantify and monitor the concentration of 1O2 and O2 consumption or recovery, so as to evaluate the therapeutic efficacy of PDT in vivo. Hence, this 1O2 activated NIR‐II CL/FL probe provides an efficient ratiometric optical imaging platform for real‐time evaluating PDT effect and precisely guiding the PDT process in vivo. A 2SeFT‐PEG/Ce6 micelle with 1O2‐triggered ratiometric NIR‐II chemiluminescence (CL)/fluorescence (FL) imaging performance to monitor and guide cancer photodynamic therapy (PDT) is developed. This study provides a method for detecting 1O2 and ratiometric NIR‐II CL and FL imaging to guide the tumor PDT process. It opens up prospects for the development of PDT imaging technology and may become an important way for the development of brand‐new PDT applications and individualized treatment for patients.